2017
DOI: 10.4038/sljch.v46i3.8319
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study on the use of bubble CPAP in a level 2 neonatal intensive care unit in Bangalore, India

Abstract: Background: Respiratory distress syndrome (RDS) is an important cause of mortality and morbidity in preterm infants. An effective way to reduce the incidence of chronic lung injury is to use continuous positive airway pressure (CPAP) and avoid mechanical ventilation. Objective:To assess the effectiveness of bubble CPAP (BCPAP) on immediate outcome of preterm infants with mild to moderate RDS in a level 2 neonatal intensive care unit (NICU) in Bangalore, India.Method: A prospective analytical study was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…A statistically significant association was found between bubble CPAP success and gestational age. Similar significant association was found with 32-34 weeks in Parasuramappa et al study [13] . This was similar to the findings in Urs et al [14] .…”
Section: Gestational Agesupporting
confidence: 83%
See 2 more Smart Citations
“…A statistically significant association was found between bubble CPAP success and gestational age. Similar significant association was found with 32-34 weeks in Parasuramappa et al study [13] . This was similar to the findings in Urs et al [14] .…”
Section: Gestational Agesupporting
confidence: 83%
“…In the present study the success rates in males and females were 73.50% and 61.50%. Parasuramappa et al study [13] showed a success rate of 61.5% in males & 38.5% in females. In Singh et al, [10] success rates were 55.6% & 4.4% in males and females respectively.…”
Section: Gendermentioning
confidence: 91%
See 1 more Smart Citation